Violencia intrafamiliar y su influencia en el rendimiento académico en una niña de 10 años - Chica Bustamante, Catherine Johanna (2020)
The work presented in this document is a case study that addresses how domestic violence, mainly of a verbal type, has influenced the academic performance of a 10-year-old girl and that through the diagnostic procedure we were able to establish the type of pathology that her It already affected her family system, with this we proceeded to recommend the application of a therapeutic scheme oriented in cognitive-behavioral and systemic therapies from which significant improvements were obtained both in the behavior of the girl and in the relationships with her family system.